MODEL GAYA KEPEMIMPINAN TRANSFORMATIF DALAM MENINGKATKAN DAYA SAING PENDIDIKAN DI ERA INDUSTRI 4.0 - Safi'i, Asrop (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
Organizational culture at the school level requires leaders who are creative, in mobilizing madrasah, so that the learning carried out becomes meaningful and produces quality education. Transformative leadership design model is needed as an effort to produce education that is competitive and produces students who have personality integrity, a disciplined attitude, are creative, innovative and competitive. This article seeks to elaborate on the transformative leadership model of madrasah headmaster in increasing the competitiveness of education in the industrial era 4.0 with the object of Madrasah Aliyah. Using library research, this article argues that transformative leaders have several indicators: first, the existence of team work that collaborates across the entire academic community. Second, there is an increase in teacher work ethic, thereby fostering teacher professionalism. Third, it enables the implementation of the supervisory leadership role. Fourth, creating madrasah organizational arrangements, a relationship climate that is loose coupling, and changing the structure and climate of the bureaucracy to a comfortable professional bureaucracy so as to enable the implementation of organizational leadership roles.